Earlier Diagnosis of Progressive Disease during Bevacizumab Treatment Using O-(2-F-Fluorethyl)-L-Tyrosine Positron Emission Tomography in Comparison with Magnetic Resonance Imaging - Norbert Galldiks; Marion Rapp; Gabriele Stoffels; Veronika Dunkl; Michael Sabel; Karl-Josef Langen (Molecular Imaging)
Antiangiogenic treatment using bevacizumab in brain tumor patients may cause difficulties in the diagnosis of tumor progression (ie, nonenhancing tumor progression). Newly defined criteria for treatment assessment and diagnosis of tumor progression (ie, RANO [Response Assessment in Neuro-Oncology] criteria) have implemented signal alterations on T 2 /fluid-attenuated inversion recovery (FLAIR) sequences to changes in contrast enhancement. However, T 2 /FLAIR hyperintensity may be influenced by other causes (eg, radiation-induced leukoencephalopathy, peritumoral edema, gliosis). Positron emission tomography using the radiolabeled amino acid O-(2-[ 18 F]fluoroethyl)-L-tyrosine ( 18 F-FET-PET) may help detect the metabolically active tumor extent. We present 18 F-FET-PET imaging findings in a glioblastoma patient during bevacizumab treatment suggesting an earlier diagnosis of tumor progression than magnetic resonance imaging changes, which are based on the RANO criteria.